A tomada de decis??o em projetos: um estudo explorat??rio sobre o processo de identifica????o de riscos - Napolitano, Domingos M??rcio Rodrigues (2014)
The decisions are central space within organizations and become more complex under conditions of uncertainty. This implies that to meet the demand for the success and quality of decisions should establish a decision-making process that will have as core elements of these decisions the scenarios, the alternatives and their impacts . On the other hand the theory and practice of project management seeks to manage risks through tools and techiniques that enable project managers perform choices on the actions that enable to achieve project objectives. In this sense, there are many studies that suggest the influence of risk management practices in successful projects. Risk management consists of planning, identification, analysis, planning responses and monitoring and control. The importance of the identication process is dependent on the subsequent phases of all their results and the decisions made about them. So when identifying risks decisions that enable their treatment aiming the project's success will be needed. In this context, the present work studied the influence of risk identification in the decisions about the risks in projects. The study was based on a literature review of risk management in projects and the characteristics of decision-making in risky situations , which made it possible to operationalize a construct and respctivas study hypotheses . Thus, it was defined a research tool outlined by a survey type lift, for which valid responses were obtained 35. Results were analyzed using statistical techniques, confirmed that two of the three hypotheses. The main findings were that, at least for the sample studied, the practices of the risk identification process project risk influence decisions on projects, which may be based on basic elements of decision theory. In this sense it was also found that these same practices positively influence the effectiveness of decisions at least in the way they are perceived by the respondents of the questionnaire. The data analysis it was observed that there is a tendency to frequent use of elements of project planning and timelines and cost estimates, but the same was not observed in the use of specific tools and techniques of risk management. With respect to decisions we observed that there is a tendency to consider the cost impacts more frequently than the impacts in time, scope or quality. Are recommended further work on the issue of the relationship between risk management practices and decisions of project managers in the bibliography since there have been few studies on the subject.